How to write science fiction and fantasy - Card, Orson Scott frey50 (Cincinnati, Ohio Writer's Digest Books, 2001)
You've always dreamed of writing science fiction and fantasy--tales that pull readers into extraordinary new worlds and fantastic conflicts. Best-selling author Orson Scott Card show you how it's doing
Introduction -- Chapter 1 The infinite boundary -- Chapter 2 World Creation -- Chapter 3 Story Construction -- Chapter 4 Writing well -- Chapter 5 The life and business of writing
Includes Index
Keywords: Science fiction -- Authorship; Science fiction -- Technique; Fantasy literature -- Authorship; Fantasy literature -- Technique; Creative writing